Method for spray forming an object

The method of cold spraying and sintering metal powder mixtures addresses bonding issues in cold spray processes, enhancing the strength and mechanical properties of 3D objects by improving particle adhesion and reducing porosity.

JP7610504B2Active Publication Date: 2025-01-08EFFUSIONTECH IP PTY LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021523616
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-11-09
Filing Date
2019-10-22
Publication Date
2025-01-08
Estimated Expiration
2039-10-22

AI Technical Summary

Technical Problem

Existing cold spray processes face issues with incomplete bonding of metal particles, leading to insufficient strength in the final product due to metallurgical discontinuities and low deposition efficiency of hard alloys, which can be costly and time-consuming to address.

Method used

A method involving cold spraying a mixture of metal powders, followed by sintering at temperatures above the minimum melting point of the alloy to liquefy and solidify a portion of the sprayed powder, enhancing bonding and reducing spacing between particles.

Benefits of technology

The method improves the strength and bonding of cold-sprayed objects by reducing porosity and non-adhesion, resulting in higher tensile strength and better mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610504000008
    Figure 0007610504000008
  • Figure 0007610504000009
    Figure 0007610504000009
  • Figure 0007610504000010
    Figure 0007610504000010
Patent Text Reader

Abstract

The present invention relates to a method of forming a three-dimensional solid object, the method comprising the steps of: a) cold spraying one or more metal powders to form a solid three-dimensional article; b) thermally sintering the article so that a portion of the sprayed powder liquefies and reduces the spaces between one or more solid portions of the article and / or their non-adhesion; and c) causing or allowing the portion of the liquefied sprayed powder to become solid upon heating.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THEINVENTION The present invention relates to a method for spray forming objects, for example by cold sprayed powder. [Background technology]

[0002] background Cold spraying of metal powders to form 3D products is well known. The process can be considered a type of 3D printing. The powder is typically carried by an accelerant gas and sprayed from a nozzle of a handheld gun or robotic device to form or repair the product or part thereof.

[0003] A problem associated with at least many cold spray processes is incomplete bonding of the deposited metal particles resulting in a final product with insufficient strength. It is believed that this may be due to metallurgical discontinuities between bonded portions of the sprayed particles. For example, excessive voids or unfilled voids may remain between the deposited particles. Furthermore, a significant portion of the particle surface may not bond with adjacent particles. To address these issues, the powder may be sprayed more vigorously, for example by increasing the velocity, increasing the temperature, or compressing the sprayed powder by hot isostatic pressing. While these measures may ameliorate the shortcomings, they may also increase production costs to an unacceptable level.

[0004] Another problem is that alloys with favorable mechanical hardness can be very difficult to deposit using cold spray because the powder itself is very hard, resulting in poor powder retention (i.e., poor deposition efficiency). This problem can sometimes be rectified by annealing the powder, but this is time consuming and expensive.

[0005] The use of metallurgical techniques to form objects from metal powders is also known. These involve compressing the metal powder before or while it is being heated. The combination of compression and heat serves to bind the powder together in a closed or open die, or the powder is first compressed and then heated to produce a solid metal object.

[0006] In some cases, the powder is first lightly compressed in a closed die, then heated and smashed into a second die (known as powder forging), but such dies can be undesirably expensive and time-consuming to manufacture. Summary of the Invention [Problem to be solved by the invention]

[0007] Object of the invention It is an object of a preferred embodiment of the present invention to go at least to some extent toward addressing the above problems. This object applies to the preferred embodiment, but should not be viewed as limiting the scope of the claims, which are more broadly expressed. In this regard, the object of the present invention itself is merely to provide the public with a useful choice.

[0008] definition When used herein in reference to a combination of steps or features, the term "comprising" should not be construed as excluding the option that other unspecified steps or features are present, and thus the term should be interpreted as non-exclusive.

[0009] As used herein, the term "cold spray" means spraying a powder from a nozzle at a temperature below the melting point of the powder and at a velocity high enough to form a bond when the powder impacts a target. [Means for solving the problem]

[0010] Summary of the Invention According to one aspect of the invention, there is provided a method of forming a three-dimensional solid object, comprising the steps of: a) cold spraying one or more metal powders to form a three-dimensional solid article; b) sintering the article so that a portion of the sprayed powder liquefies and reduces spaces and non-adhesion between one or more solid portions of the article; c) causing or allowing a portion of the liquefied sprayed powder to become solid upon heating; A method is provided that includes:

[0011] Optionally, the sprayed powder comprises a mixture of a major powder, which is at least the primary matrix-forming powder, and a minor powder, which is at least the sintering powder.

[0012] Optionally, the major powder and / or the minor powder each comprise an alloy.

[0013] Optionally, in step b), the article is heated to a temperature above the minimum melting temperature of the alloy formed by the matrix-forming powder and the sintering powder.

[0014] Optionally, in step b), the article is heated to and held at one or more temperatures below the minimum melting temperature of the alloy formed by the matrix powder and the sintering powder before exceeding such temperature.

[0015] Optionally, the shape of the article when formed is substantially determined by the matrix-forming powder.

[0016] Optionally, in step b), substantially only the sintering powder is liquefied.

[0017] Optionally, the matrix-forming powder comprises: a) less than 3% by weight; b) less than 2.2% by weight; or c) Less than 1.5% by weight The additional metal content is:

[0018] Optionally, at least a majority of the matrix-forming powder comprises primarily at least one or more of aluminum, copper, nickel, iron, and / or a 6000 series aluminum alloy.

[0019] Optionally, the matrix-forming powder comprises a ceramic material.

[0020] Optionally, the sintering in step b) is with a sintering powder mainly comprising one or more of the metals aluminum, copper, nickel, tin and zinc.

[0021] Optionally, the sintering in step b) comprises: a) less than 15% by weight of the powder sprayed; b) less than 10% by weight of the sprayed powder; or c) Less than 5% by weight of the sprayed powder This is due to the sintering powder.

[0022] Optionally, the combination of matrix-forming powder and sintering powder has a minor portion of an element that provides sintering in step b), the minor portion comprising one or more of magnesium, silicon, carbon, nickel, copper, zinc, tin, aluminum, lithium, chromium, iron and manganese.

[0023] Aluminum, Al-Si-Mg alloy and copper powder Optionally, the sprayed powder consists of or comprises aluminum (e.g., in a 6000 series alloy), an Al-Si-Mg alloy, and copper, and in step b) the article is a) at 524-610°C, optionally for at least 1-7 hours; b) held at 470-550°C; c) Cooled so that the alloying elements are in saturated solid solution.

[0024] Optionally, the sprayed powder consists of or comprises aluminum (e.g., 6000 series alloys), Al-Si-Mg alloys and copper, and in step b) the article is a) at 450-525°C, optionally for 15-300 minutes; b) at 524-610°C, optionally for at least 1-7 hours; c) held at 470-550°C; d) Cooled so that the alloying elements are in saturated solid solution.

[0025] Copper and aluminum powder Optionally, the sprayed powder consists of or comprises copper and aluminum (up to about 15% aluminum by weight), and in step b) the article is held at 850-1000° C., optionally for at least 8-16 hours.

[0026] Optionally, the sprayed powder consists of or comprises copper and aluminum (up to about 15% by weight aluminum), and in step b) the article is a) at 325-400°C, optionally for at least 4-18 hours; b) at 850-1000° C., optionally for at least 8-16 hours.

[0027] Optionally, the sprayed powder consists of or comprises copper and aluminum (optionally up to about 15% by weight aluminum), and in step b) the article is a) at 325-400°C, optionally for at least 4-18 hours; b) at 850-1,000°C, optionally for at least 8-16 hours; c) held at 800-1000°C; d) Cooled so that the alloying elements are in saturated solid solution.

[0028] Copper, aluminum, iron and nickel or silicon powder Optionally, the sprayed powder consists of or comprises copper and aluminum (optionally up to about 15% aluminum by weight), with up to 4% iron and up to 3% nickel or silicon.

[0029] Copper and zinc powder Optionally, the sprayed powder consists of or comprises copper and zinc (optionally up to about 15% by weight zinc), and in step b) the article is held at 850-950° C., optionally for at least 8-14 hours.

[0030] Optionally, the sprayed powder consists of or comprises copper and zinc (optionally up to about 15% by weight zinc), and in step b) the article is a) at 320-400°C, optionally for at least 1-8 hours; b) at 850-950°C, optionally for at least 8-14 hours.

[0031] Optionally, the sprayed powder consists of or comprises copper and zinc (optionally up to about 15% by weight zinc), and in step b) the article is a) at 320-400°C, optionally for at least 1-8 hours; b) at 420-550°C, optionally for at least 5-25 minutes; c) at 850-950°C, optionally for at least 8-14 hours.

[0032] Copper and tin powder Optionally, the sprayed powder consists of or comprises copper and tin (optionally up to about 10% by weight tin), and in step b) the article is held at 850-950° C., optionally for at least 8-14 hours.

[0033] Optionally, the sprayed powder consists of or comprises copper and tin (optionally up to about 10% by weight tin), and in step b) the article is a) at 200-230° C., optionally for at least 1-8 hours; b) at 850-950°C, optionally for at least 8-14 hours.

[0034] Optionally, the sprayed powder consists of or comprises copper and tin (optionally up to about 10% by weight tin), and in step b) the article is a) at 231-400°C, optionally for at least 5-25 minutes; b) at 850-950°C, optionally for at least 8-14 hours.

[0035] Copper and iron powder Optionally, the sprayed powder consists of or comprises iron and copper (optionally up to about 5% by weight copper), and in step b) the article is held at 1,096-1,200° C., optionally for at least 8-14 hours.

[0036] Optionally, the sprayed powder consists of or comprises iron and copper (optionally up to about 5% by weight copper), and in step b) the article is a) at 800 to 1,096°C, optionally for at least 1 to 8 hours; and b) at 1,096-1,200° C., optionally for at least 8-14 hours.

[0037] Optionally, the sprayed powder consists of or comprises iron and copper (optionally up to about 5% by weight copper), and in step b) the article is a) at 1,096-1,200°C, optionally for at least 8-14 hours; b) held at 750-900°C, and then, optionally, c) cooled to produce a martensitic structure.

[0038] Iron and Nickel Powder Optionally, the sprayed powder consists of or comprises iron and nickel (optionally up to about 5 wt. % nickel), and in step b), the article is held at 1,455-1,490° C., optionally for at least 8-14 hours.

[0039] Optionally, the sprayed powder consists of or comprises iron and nickel (up to about 5% by weight nickel), and in step b) the article is a) at 1,000 to 1,455°C, optionally for at least 1 to 8 hours; b) at 1,455-1,490°C, optionally for at least 8-14 hours.

[0040] Optionally, the sprayed powder consists of or comprises iron and nickel (up to about 5% by weight nickel), and in step b) the article is a) at 1,455-1,490°C, optionally for at least 8-14 hours; b) held at 750-900°C; c) cooled to produce a martensitic structure.

[0041] Nickel and copper powder Optionally, the sprayed powder consists of or comprises nickel and copper (up to about 15% by weight copper), and in step b) the article is held at 1,100-1,300° C., optionally for at least 8-14 hours.

[0042] Optionally, the sprayed powder consists of or comprises nickel and copper (up to about 15% by weight copper), and in step b) the article is a) at 900-1,100°C, optionally for at least 1-8 hours; b) at 1,100-1,300° C., optionally for at least 8-14 hours.

[0043] Any powder Optionally, the sprayed powder in step a) consists of or comprises spheroidal particles, such as spheres or oblate spheroids.

[0044] Optionally, the sprayed powder in step a) consists of or comprises particles that are not irregular, sharp or rough.

[0045] Optionally, the sprayed powder in step a) consists of or comprises particles, at least 90% of which are between 15 and 80 μm in overall length (eg, diameter).

[0046] Optionally, the sprayed powder in step a) consists of or comprises particles, at least 90% of which are between 15 and 45 μm in overall length (eg, diameter).

[0047] Optionally, the matrix-forming powder has a hardness of less than 200 HV.

[0048] Optionally, the matrix-forming powder has a hardness of less than 150 HV.

[0049] Optionally, the matrix-forming powder has a hardness of less than 100 HV.

[0050] image Some preferred embodiments of the invention will now be described, by way of example only, with reference to the accompanying images. [Brief description of the drawings]

[0051] [Figure 1] 1 is a phase diagram of copper. [Diagram 2] Photographs show a series of blocks produced by cold spraying of a mixture of Al-Si10-Mg powder + 3% Cu powder. [Diagram 3] FIG. 1 is a phase diagram of an Al-Si10-Mg alloy. [Figure 4] Further blocks produced by cold spraying of a mixture of Al-Si10-Mg alloy + 3% Cu are shown in the photograph. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0052] Detailed Description A variety of three-dimensional objects were formed by cold spray, the details of which are described below. EXAMPLES

[0053] Example 1 Cold sprayed aluminum alloy 6061 powder Aluminum alloy 6061 is a commercial product as described, for example, at https: / / en.wikipedia.org / wiki / 6061_aluminium_alloy.

[0054] Aluminum alloy 6061 has a strength of about 2.7 g / cm 3 It may be used as a solid "extensible" product with a density of about 1.0 mm, a melting point of about 580 °C, an elastic modulus of about 70 to 80 GPa, a Poisson's ratio of about 0.33, a thermal conductivity of about 173 W / m K, and an electrical resistivity of about 3.7 to 4.0 × 10-6 Ω cm.

[0055] Aluminium alloy 6061 is available in Australia as a powder from Ecka Granules Germany, a subsidiary of Kymera International (https: / / www.kymerainternational.com / ) and has a composition substantially as shown in the table below.

[0056] [Table 1]

[0057] Cold sprayed powder aluminum alloy 6061 is often substandard for wrought grades in terms of tensile strength of the final product, likely due to incomplete grain bonding within and / or between sprayed layers in the microstructure of the cold sprayed article.

[0058] A series of standard tensile specimens were prepared by cold spraying aluminium alloy 6061 powder using compressed air at 30 bar and 500° C. These were heat treated as follows: Annealing: 575℃ x 4 hours + air cooling Solution treatment: 530℃ x 1 hour + water quenching Aging: 200℃ x 1 hour

[0059] The specimens were then tested for break and elongation with average results as shown in the table below, which also provides a comparison with wrought aluminum alloy 6061.

[0060] [Table 2]

[0061] As shown in the table, articles can be effectively cold sprayed from aluminum alloy 6061 powder, and although they will deposit and form effectively, the particles involved will not bond as well and will not provide the same strength as wrought aluminum.

[0062] Example 2 Cold sprayed aluminum alloy 6061 powder + 4% Cu powder Copper particles were found to deposit well when cold sprayed, but pure copper appears to have no or poor ability to heat harden, and so is generally considered to be of limited use in structural applications, making it an unlikely candidate for cold spraying of articles that need to have sufficient strength.

[0063] However, the inventors have discovered that copper powder can be cold sprayed in combination with aluminum alloy 6061 powder to good effect. It has been found that when sprayed in a mixture with aluminum alloy 6061 powder, copper powder forms a liquid phase at temperatures above 548°C, resulting in a 3D product (as shown in Figure 1). Surprisingly, it has been discovered that copper results in a much harder final article than aluminum alloy 6061 powder alone. It has been found that copper has a moderate diffusion coefficient with respect to aluminum, so that copper can form a liquid phase that sinters quickly and does not tend to simply dissolve in the aluminum matrix.

[0064] A series of standard tensile specimens were formed by cold spraying a mixture of aluminum alloy 6061 powder and 4% Cu powder by weight using compressed air at 30 bar and 500° C. These were heat treated as follows: Sintering: 610℃ x 3 hours + furnace cooling Solution treatment: 505℃ x 1 hour + water quenching Aging: 160℃ x 1 hour

[0065] The resulting material was tensile tested and found to have significantly higher strength, as shown in the table below, including a comparison with the results of Example 1.

[0066] [Table 3]

[0067] The article of Example 2, i.e., the article with copper in the mixture, was much stronger than the article of Example 1 and nearly as strong as the wrought article. In summary, the addition of copper powder along with the "post-spray heat treatment" greatly improved the break stress and elongation parameters.

[0068] Example 3 The porosity of 6061+4%Cu varies depending on the heat treatment Referring to FIG. 2, a series of blocks were formed by cold spraying a mixture of aluminum alloy 6061 powder and 4% Cu powder by weight at 30 bar and 500° C.

[0069] They were then heat treated as follows.

[0070] [Table 4]

[0071] As shown in Figure 2, sample A showed no visible porosity. However, samples B and C showed substantial overall porosity during heat treatment, causing their densities to decrease and making the final articles unsuitable for many mechanical applications. In contrast, sample D surprisingly showed no visible porosity, making it a candidate for mechanical applications.

[0072] Example 4 Al-Si10-Mg+3%Cu cannot be cold sprayed. A common powder alloy for 3D printing (e.g., selective laser melting) is Al-Si10-Mg, a typical composition of which is shown below:

[0073] [Table 5]

[0074] The Al-Si10-Mg alloy is designed to melt and was believed to be suitable for liquid phase sintering in the context of cold spraying. As shown in Figure 3, it has a large two-phase region suitable for liquid formation (e.g., a large temperature zone where it can become solid or liquid). Furthermore, it can be hardened in a manner similar to sprayed aluminum alloy 6061. The addition of Cu was believed to be sufficient to reduce the temperature at which the sintering liquid is initially present to 524°C (Figure 2). This was believed to promote the liquid phase sintering process and enhance the hardening response upon final heat treatment as described above.

[0075] To carry out the aforementioned tests, blocks of material were cold sprayed using a mixture of Al-Si10-Mg powder and 3% Cu powder by weight. The powder was applied using air at 30 bar and 500°C. However, as shown in Figure 4, the blocks did not form properly. The reason for this was that Al-Si10-Mg was found to have a low deposition efficiency in that only about 15% of the sprayed material was successfully incorporated into the block, the rest bounced off. This surprising poor result was due to an excessive proportion of hard silicon in the aluminum powder.

[0076] Example 5: Surprising performance achieved by pre-sintering 6061+5%Al-10Si-Mg+1%Cu The 6061 alloy powders of Examples 1 and 2 were mixed with 5% Al-10Si-Mg and 1% Cu and then cold sprayed. The sprayed parts were subjected to non-conventional heat treatments, including a "pre-sintering" treatment as follows: Pre-sintering: 500℃ x 20 minutes Sintering: 595℃ x 4 hours Solutionizing: 530℃ x 1 hour + water quenching

[0077] The sample was then aged at 150°C for 2.5 hours.

[0078] This returned significant results, as shown in the table below.

[0079] [Table 6]

[0080] Example 6: Application of pre-sintering to aluminum bronze Without wishing to be bound by theory, it is believed that the pre-sintering treatment in Example 5 can improve liquid penetration along poorly bonded interfaces and reduce porosity, an effect that can be generalized to various alloy systems, such as aluminum bronze.

[0081] Pure copper powder was mixed with 10% 6061 powder from Examples 1 and 2. This was cold sprayed into parts that were then heat treated in two ways as per the table below and then tested. Additionally, for comparison, fully alloyed aluminum bronze powder (i.e. no sintering agent) was cold sprayed and tested. The mixed powder with the two pre-sintering steps performed very well.

[0082] [Table 7]

[0083] In terms of the disclosure, the specification hereby contemplates and discloses each article, step, or other feature referred to in this specification in combination with any one or more of other articles, steps, or other features disclosed in this specification, regardless of whether such combination is claimed in each instance.

[0084] While certain preferred forms of the invention have been described by way of example, it should be understood that modifications and improvements are possible without departing from the invention or the following claims.

Claims

1. 1. A method for forming a three-dimensional solid object, comprising: Cold spraying one or more metal powders to form a three-dimensional solid article, the powders including a mixture of a matrix-forming powder and a sintering powder; The matrix-forming powder comprises: Mg: 0.8 to 1.2% by weight Si: 0.4 to 0.8% by weight Fe: 0.7% by weight or less Cu: 0.15 to 0.40 wt.% Zn: 0.25% by weight or less Ti: 0.15% by weight or less Mn: 0.15% by weight or less Cr: 0.04 to 0.35% by weight a first aluminum alloy powder containing Al and the remainder being Al; Mg: 0.25 to 0.35% by weight Si: 9.5 to 10.5% by weight Fe: 0.7% by weight or less Cu: 0.05% by weight or less Zn: 0.25% by weight or less Ti: 0.15% by weight or less Mn: 0.15% by weight or less Cr: 0.04 to 0.35% by weight and a second aluminum alloy powder containing Al as the balance, The first aluminum alloy powder is mixed with 5% by weight of the second aluminum alloy powder, The sintering powder is Cu, The mixture is a mixture of the matrix forming powder and 1% by weight of the sintering powder; sintering the article so that a portion of the sprayed metal powder liquefies and reduces at least one of the spaces and non-adhesion between one or more solid portions of the article; An alloy formed by the matrix forming powder and the sintering powder is Maintain at 500°C for at least 20 minutes, A sintering step at a temperature above 500° C. for at least 4 hours; maintaining the article at 530° C. for at least one hour or more to solidify the portion of the liquefied sprayed metal powder; A method comprising:

2. The method of claim 1 , wherein the shape of the formed article is determined by the matrix-forming powder.

3. The method according to claim 1 or 2, wherein in the sintering step, only the sintering powder is liquefied.

4. 1. A method for forming a three-dimensional solid object, comprising: Cold spraying one or more metal powders to form a three-dimensional solid article, the powders including a mixture of a matrix-forming powder and a sintering powder; The matrix-forming powder comprises: Mg: 0.8 to 1.2% by weight Si: 0.4 to 0.8% by weight Fe: 0.7% by weight or less Cu: 0.15 to 0.40 wt.% Zn: 0.25% by weight or less Ti: 0.15% by weight or less Mn: 0.15% by weight or less Cr: 0.04 to 0.35% by weight and the balance comprises Al, The sintering powder is Cu, The mixture is a mixture of the sintering powder and 10% by weight of the matrix-forming powder; sintering the article so that a portion of the sprayed metal powder liquefies and reduces at least one of the spaces and non-adhesion between one or more solid portions of the article; An alloy formed by the matrix forming powder and the sintering powder is Maintain at 325°C for at least 16 hours; A sintering step at 555°C for at least 30 minutes; maintaining the article at 950° C. for at least 16 hours or more to solidify the portion of the liquefied sprayed metal powder; A method comprising:

5. The method of claim 4 , wherein the shape of the formed article is determined by the matrix-forming powder.

6. 6. The method according to claim 4 or 5, wherein in the sintering step only the sintering powder is liquefied.

7. 1. A method for forming a three-dimensional solid object, comprising: cold spraying one or more metal powders to form a three-dimensional solid article, the metal powders including a matrix forming powder and a sintering powder, the metal powders being a mixture of copper and at least 15 weight percent aluminum by weight; sintering the article so that a portion of the sprayed metal powder liquefies and reduces at least one of the spaces and non-adhesion between one or more solid portions of the article; An alloy formed by the metal powder, Maintaining at 325-400°C for 4-18 hours; A sintering step at 850-1000°C for 8-16 hours; maintaining the article at 800-1000°C to solidify the portion of the liquefied sprayed metal powder; A method comprising:

8. The sprayed metal powder in the step of forming a three-dimensional solid article comprises: a) spheroidal particles, including spheres or oblate spheroids, and b) particles that are not irregular, sharp, or rough; and c) particles, at least 90 percent of which are between 15 and 80 μm in total length (diameter); and d) particles, at least 90 percent of which are between 15 and 45 μm in total length (diameter); The method according to any one of claims 1 to 7, comprising or consisting of at least one of:

9. The method according to any one of claims 1 to 8, wherein the matrix-forming powder has a hardness of less than 200 HV.

10. The method according to any one of claims 1 to 9, wherein the matrix-forming powder has a hardness of less than 150 HV.

11. The method according to any one of claims 1 to 10, wherein the matrix-forming powder has a hardness of less than 100 HV.

Citation Information

Patent Citations

  • Production of aluminum sintered compact

    JP1994212313A

  • Method for freely molding metallic component

    JP1997111308A

  • METHOD FOR FORMING METAL MATRIX COMPOSITE AND COATING LAYER AND BULK PRODUCED USING THE SAME

    JP2008538385A

  • Method for manufacturing laminate member

    JP2018123405A

  • Cold gas spray coating method and composition

    JP2018524466A